Erdheim‐Chester disease: A multisystem disease case illustration with rare manifestations and treatment challenges. Issue 2 (24th February 2023) - Jridi, Maysam; Ben Achour, Tayssir; Naceur, Ines; Smiti, Monia; Ben Ghorbel, Imed; Lamloum, Mounir; Said, Fatma; Houman, Mohamed Habib
Abstract: Erdheim‐Chester disease is a rare multisystemic disease. A 50‐year‐old woman, presented with a recurrent pain and swelling of the left knee. Bone scintigraphy showed increased tracer uptake of peripheral skeleton. The computed tomography showed tissular infiltration in the retroperitoneum, around the vessels. Immunohistochemistry showed CD68 (+) and CD1a (−). Abstract : Erdheim‐Chester disease has heterogenous clinical presentations. Patients may present with atypical manifestations and multisystemic involvement. Treatment can be challenging especially in low‐income countries with on board therapies.